Effect of Seed Coating with Streptomyces sp. CU-02 on Quality and Control Damping-Off in Chinese Cabbage (Brassica rapa, subsp. pekinensis) - Sansupa, Nilamai; Kangsopa, Jakkrapong; Yangkhamman, Pranom; Phuakjaiphaeo, Chatsuda (YRU Journal of Science and Technology, 2021)
Farmers usually use chemical substances to control damping-off in Chinese cabbages which cause contamination risks for farmers and consumers, as well as pollution of the environment. This research focuses on studying the control of damping-off using biological controls to replace the use of chemical substances. The antagonistic microorganisms Streptomyces sp. is used to test its efficiency in promoting growth of Chinese cabbage seeds and controlling damping-off caused by P. aphanidermatum. The test design is based on the completely randomized design (CRD) with four repetitions using five seed coating methods which are 1) uncoated seeds, 2) seeds coated with CMC mixed Streptomyces sp. CU-02 at various concentrations, which is defined as 3) 1x106, 4) 1x107 and 5) 1x108 spore ml-1/10 g. After testing the quality of Chinese cabbage seeds under greenhouse conditions, it was found that Chinese cabbage seeds coated with all levels of Streptomyces sp.CU-02 had better germination, speed of germination index; (SGI), and mean germination time (MGT) compared to uncoated seeds and seeds coated with CMC. Meanwhile, in terms of the efficiency of Streptomyces sp. CU-02 in controlling damping-off, it was found that a 1x106 spore ml-1of Streptomyces sp. CU-02 is efficient in controlling damping-off since a lower percentage of seed rot and higher percentage of healthy seedlings were found compared with other test methods.